The Relation Among Reactive Stepping and Fall-Related Psychological Factors in Multiple Sclerosis - Taylor N. Takla; Patrick G. Monaghan; Daniel S. Peterson; Nora E. Fritz (Brain Sciences)
Purpose: Persons with multiple sclerosis (MS) experience changes in balance, such as poor and reactive stepping, as well as altered fall-related psychological factors, such as increased concern about falling and feared consequences about falling. Such concerns and fear may relate to and influence mobility. However, these relations are poorly understood in people with MS. This study aimed to investigate the relation between reactive stepping performance and fall-related psychological factors, as well as to assess how these relations differ between individuals who have and have not fallen. Methods: In a single session, participants completed measures regarding fall-related psychological factors (balance confidence, concern about falling, and feared consequences of falling) and completed reactive stepping tasks. Following the visit, participants completed weekly surveys for 3 months to report their falls. Spearman rho correlations were computed to examine associations between participants’ reactive stepping performance and their fall-related concerns, confidence, and consequences, with a stratified analysis to compare these associations between fallers and non-fallers. Results: 44 individuals with MS participated in our study, with 27 individuals experiencing 0 falls (non-fallers) and 17 individuals experiencing at least 1 fall (fallers) in the 3-month follow-up period. Better reactive stepping performance was correlated with fewer concerns, greater confidence, and lower feared consequences related to falling. The stratified analysis revealed a greater number of significant associations for non-fallers than fallers, although the small sample of fallers reduced our ability to detect a relationship in this group. Conclusions: Reactive stepping was associated with fall-related psychological factors. Interventions targeting reactive stepping may be beneficial in enhancing fall-related psychological well-being in the MS community.